PENGARUH PENGETAHUAN INVESTASI, RISIKO INVESTASI, DAN MOTIVASI INVESTASI TERHADAP MINAT BERINVESTASI PADA PASAR MODAL SYARIAH - Moh. Joko Prasetyo; Deny Yudiantoro; Amalia Nuril Hidayati (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
This research data research aims to find the impact of investment knowledge, investment risk, and investment motivation on the investment interest of students in the Islamic capital market in Islamic Financial Management students at UIN Sayyid Ali Rahmatullah class of 2018-2019. The approach in this study using a quantitative approach. The data collection technique in this study used the technique of distributing questionnaires. Sources of data in this study with primary data amounting to 90 student respondents. The collected data was then tested with several SPSS tests which included reliability test, multiple linear regression test, data normality test, multicollinearity test, heteroscedasticity test, partial T test, and simultaneous F test. The findings of the data in this study indicate that the investment knowledge variable (X1) has an influence on students' interest in investing in the Islamic capital market. Partially, the investment risk variable (X2) has no effect on students' interest in investing in the Islamic capital market. Partially, the investment motivation variable (X3) has an influence on students' interest in investing in the Islamic capital market.